Direct determination of lead isotopes (206Pb, 207Pb, 208Pb) in Arctic ice samples at picogram per gram levels using inductively coupled plasma-sector field MS coupled with a high-efficiency sample introduction system - Krachler, Michael; Zheng, Jiancheng; Fisher, David; Shotyk, William (Analytical chemistry, 2004)
Adopting strict cleanroom procedures, ice samples from the Canadian High Arctic have been analyzed for Pb concentrations and Pb isotopes (206Pb, 207Pb, 208Pb) using ICP-SMS. The detection limit for Pb (0.06 pg g-1) was ∼2 orders of magnitude lower than the lowest concentration of Pb in the ice samples (range, 4.3−1660 pg g-1; median, 45 pg g-1). Acidification of ice samples with high-purity HNO3 for stabilization purposes contributed only 0.004 pg of Pb g-1, which is an insignificant source of Pb. Using a new sample introduction system consisting of a heated (140 °C) minicyclonic spray chamber and a Peltier cooled condenser (2 °C) and by replacing the conventional sample cone with a high-performance cone, signal intensities for Pb were increased by ∼1 order of magnitude. Thus, it was possible not only to measure Pb isotope ratios directly using ICP-SMS but also to achieve reasonable precision (∼0.2%) at low picogram per gram concentrations of total Pb. This precision is comparable to that achievable by thermal ionization mass spectrometry at such low Pb concentrations, but the ICP-SMS requires much less sample volume (∼2 mL), needs no sample pretreatment, and therefore is considerably faster and less expensive than the conventional approach. Even though absolute Pb concentrations in two ice samples dating from 1974 and 1852 were very similar (9 and 6 pg g-1) their fundamentally different isotopic signature (206Pb/207Pb:  1.169 ± 0.002 vs 1.147 ± 0.003) clearly indicates different sources of Pb. The analytical procedures described here, therefore, offer great promise for fingerprinting the predominant sources of atmospheric Pb in polar snow and ice.
Gesehen am 30.09.2020
Im Titel sind die Ziffern "206", "207", "208" hochgestellt